Emerging mechanisms and implications of m6A in CVDs: potential applications of natural products - Hui Wang; Yun Zhang; Xiao Jiang; Guichun Liu; Shujian Xu; Jinbiao He; Xudong He; Ting Xiao; Lijuan Wang; LiJing Xiao; Xinhui Li (Frontiers in Cardiovascular Medicine, 2025)
N6-methyladenosine (m6A) RNA methylation is the most common, abundant, and reversible epigenetic modification of RNAs, and it directs many essential processes in RNAs post-transcriptionally. It has been shown that m6A modification affects cardiovascular diseases (CVDs) by regulating RNA splicing, localization, translation, and stabilization and regulating processes such as autophagy, apoptosis, inflammatory responses, and oxidative stress. A growing body of evidence has shown that natural products have the unique advantage of being highly effective with few side effects and have significant effects against CVDs. However, few studies have explored the relationship between natural products and m6A modification in the development of CVDs. In this review, we summarized the biological functions of m6A modification and discussed the potential mechanisms and processes of m6A modification in various CVDs; we also summarized the research progress of natural products modulating m6A modification in the treatment of CVDs. This review further elucidated the relationship between the modification of m6A methylation and CVDs, thereby contributing to the development of potential therapeutic agents from natural products.